A need to integrate pharmacological management for multimorbidity into dementia guidelines in Australia - Nagar, Sanket; Ma, Liwei; Pan, Yijun; Huynh, Andrew Liem Hieu; Tan, Edwin C. K.; Jin, Liang (Frontiers in Public Health, 2024)
Introduction: Pharmacological management is a vital aspect of dementia care. Suboptimal medication prescribing and adverse drug reactions are two of the major causes for ongoing concerns for the quality of care. This review aims to investigate the existence and comprehensiveness of Australian guidelines dedicated to supporting dementia care in the context of pharmacological management.Methods: Guideline registries and databases (EMBASE and CINAHL) were searched to identify Australian guidelines addressing pharmacological management in dementia care and to uncover barriers and considerations associated with guideline implementation.Results: Seven Australian guidelines were identified. Barriers to effective implementation were identified at individual, provider, and system levels. None of the identified guidelines provided comprehensive guidance on management of multimorbidity and polypharmacy.Discussion: Although Australian guidelines are available to guide pharmacological management in dementia, several barriers impede their effective implementation. There is an urgent need for updated guidelines that address the management of multimorbidity and polypharmacy in people living with dementia.